Suspectable Risk Factors of Congenital Anomaly in Dr. Hasan Sadikin General Hospital Bandung, Indonesia - Pradistya Syifa Yudiasari; Akhmad Yogi Pramatirta; Sharon Gondodiputro (Althea Medical Journal, 2017)
Background: Congenital anomaly is a disease of structural or functional alteration since birth. The cause of congenital anomaly is genetic, environtment, and unknown. The cause of congenital anomaly is unknown, made congenital anomaly is difficult to detect. Therefore, the objective of this study was to identify the suspectable risk factors of congenital anomaly.Methods: This was a descriptive study. About 78 samples were taken by purposive sampling from medical records of patients with congenital anomaly in pediatric surgery ambulatory unit at Dr. Hasan Sadikin General Hospital (RSHS), Bandung from September to November 2014. From the selected medical records, an interview was carried out to the parents’ patient to identify some suspectable risk factors. The collected data were analyzed and presented in tables.Results: From 78 medical records,  hirschprung disease was the highest among all type of congenital anomaly (29%). The characteristic of congenital anomaly was mothers in the age of 20–35 years (65%), fathers’ age was  more than 20 years old, family history of congenital anomaly was 1%, there was no history of previous congenital anomaly in previous pregnancy, infection history was 3%, history of medication was 11.5%, mother’s BMI was in normal term (18.5─24.9) as much as 65%, no history of radiation, there was no history of chronic alcohol. History of smoking/passive smoking was high (65%).Conclusions: Hirschprung disease is the highest rate disease in congenital anomaly and smoking is a highest suspectable risk factor contribute to congenital anomaly. DOI: 10.15850/amj.v4n2.1095